Interior Design of Dual-Function Buildings of PT. Daffa Ekspressindo Logistik Using Sketchup 3D - Afid Novendra Ardhan; Gendhy Dwi Harlyan (PT ARRUS Intelektual Indonesia, 2023)
The time development has made interior design a special need for many people in visualizing the wants and needs of the spaces to be occupied, especially for companies that own buildings to carry out various business activities. A company in Batam, namely PT. Daffa Expressindo Logistik requires a good and appropriate interior design for a company building, which is used to run two business fields, including automotive repair and logistics. Therefore, an interior design was designed for the company through qualitative research methods to obtain interior design concepts and workmanship using the MDLC method. This design concept is based on the need for interior design for buildings that are used for more than one function and for the convenience of users and visitors. The benefits that users and visitors will experience with the existence of PT. Daffa Expressindo Logistics is able to fulfill all activities to work safely, comfortably, and optimally.